Diversion Policy for Child Victims of Drug Abuse in Indonesia: A Normative Juridical Analysis - Djoko Aprianto Saputro; Muh Nasir; Abu Nawas (UIN Jakarta, 2026)
Children represent the future generation and must be granted special legal protection, particularly when they come into conflict with the law. In cases of drug abuse, children often occupy a complex position, not only as perpetrators of criminal acts but also as victims of social environment influences, family conditions, peer pressure, and exploitation by other parties. This study examines whether the mechanism for implementing diversion for children involved in narcotics offenses is in accordance with the objectives of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Law Number 35 of 2009 concerning Narcotics in Indonesia. Furthermore, it analyzes Indonesia’s criminal law policy regarding the application of diversion in addressing juvenile drug-related offenses. This research employs a normative juridical method with a descriptive-analytical approach, focusing on statutory regulations and legal principles relevant to juvenile justice and drug abuse cases. The findings indicate that children involved in drug abuse should primarily undergo rehabilitation as a form of guidance and recovery rather than be subjected to punitive sanctions. Imposing criminal penalties on children is considered disproportionate, as child drug users are essentially victims of illicit drug trafficking, especially given their vulnerable age. Judicial considerations in deciding such cases include juridical aspects such as the prosecutor’s indictment, criminal charges, witness testimonies, the defendant’s statements, and evidence presented in court, as well as non-juridical aspects, including aggravating and mitigating circumstances. Therefore, diversion policies play a crucial role in ensuring that the best interests of the child are upheld, emphasizing restorative justice and rehabilitation over punishment in handling juvenile narcotics cases. Keywords: Diversion Policy; Child Victims; Drug Abuse; Juvenile Justice System; Rehabilitation